Analysis of Mental Health on The Incidence of Depression in Pregnant Women and Postpartum Women During The COVID-19 Pandemic: A Study Literature - Monalisa, Agathista Ester; Nugroho, Amanda Permadi Putri; Azzahra, Fitria Bustan Nurfianty; Abiyyunanda, Arya Fawwaz; Herbawani, Chahya Kharin (Universitas Nusa Cendana, 2024)
Mothers who are in the period of pregnancy and childbirth are prone to experience anxiety and depression due to the change in role from an ordinary woman to a mother. The emergence of the COVID-19 pandemic has affected the mental health of pregnant and postpartum women. This study aims to describe the relationship between the mental health of pregnant women and the incidence of depression during pregnancy and childbirth, the impact of depression on pregnancy and childbirth, prevention, and treatment of depression in pregnant and postpartum women during the COVID-19 pandemic. The method used is a literature review by collecting research sources in the 2019-2023 range from online databases such as GARUDA, Google Scholar, and Science Direct. The sources collected were filtered using the PRISMA method to produce concise facts about the topics to be discussed. From 10 articles, various studies were found from several countries debating the factors that cause depression during pregnancy and childbirth such as the role of partners, family, social support, lifestyle, education, and the economy. There are depressive impacts on the mother and fetus, such as premature birth, baby blues, malnutrition, impaired brain growth, low birth weight, and stunting. Early prevention and treatment need to be done to prevent adverse effects and even further complications.